2005
DOI: 10.1016/s0002-9440(10)62492-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Candidate Oncogenes and Tumor Suppressors in Malignant Pleural Mesothelioma Using Large-Scale Transcriptional Profiling

Abstract: Malignant pleural mesothelioma (MPM) is a highly lethal, poorly understood neoplasm that is typically associated with asbestos exposure. We performed transcriptional profiling using high-density oligonucleotide microarrays containing approximately 22,000 genes to elucidate potential molecular and pathobiological pathways in MPM using discarded human MPM tumor specimens (n = 40), normal lung specimens (n = 4), normal pleura specimens (n = 5), and MPM and SV40-immortalized mesothelial cell lines (n = 5). In glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
168
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 170 publications
(185 citation statements)
references
References 57 publications
15
168
0
2
Order By: Relevance
“…47,48 Based on the analysis of mRNA microarray expression data obtained from the Oncomine database, CHCHD2 is overexpressed in a diverse group of cancers, including prostate, lung, kidney, skin, brain, mesothelium, head and neck and two types of leukemias (Table 1). [49][50][51][52][53][54][55][56][57][58][59][60][61] The upregulation of CHCHD2 in cancers along with our data showing that CHCHD2 knockdown sensitizes cancer cells to chemotherapeutic agents suggests that further research investigating CHCHD2 as a cancer biomarker or as a potential chemosensitizing drug target may be warranted.…”
Section: Chchd2 Inhibits Apoptosis Y Liu Et Almentioning
confidence: 57%
“…47,48 Based on the analysis of mRNA microarray expression data obtained from the Oncomine database, CHCHD2 is overexpressed in a diverse group of cancers, including prostate, lung, kidney, skin, brain, mesothelium, head and neck and two types of leukemias (Table 1). [49][50][51][52][53][54][55][56][57][58][59][60][61] The upregulation of CHCHD2 in cancers along with our data showing that CHCHD2 knockdown sensitizes cancer cells to chemotherapeutic agents suggests that further research investigating CHCHD2 as a cancer biomarker or as a potential chemosensitizing drug target may be warranted.…”
Section: Chchd2 Inhibits Apoptosis Y Liu Et Almentioning
confidence: 57%
“…To assess whether read counts (i.e., the number of reads that mapped to a given mRNA) can quantify relative transcript levels, we focused on six specific transcripts known to be differentially expressed in MPM and ADCA, which in combination can be used as a genomic test to distinguish the two tumor types (22,23). The calculated geometric combination of the three expression ratios of these six genes obtained through real-time PCR or microarrays can be used to distinguish MPM from ADCA.…”
Section: Resultsmentioning
confidence: 99%
“…The horizontal asymptote represents Ϸ17,000 of the Known RefSeq Genes detected by at least one read in any of the four MPM samples, which encompassed a total of 7 million reads. (B) Classification of tumor specimens using read counts to calculate gene expression ratios for six known diagnostic genes and their geometric mean (23). Ratios correctly identified each tumor type (i.e., Ͼ1, MPM; Ͻ1, ADCA).…”
Section: Rules For Single Nucleotide Substitution Variant (Snv) ‡ ‡ Dmentioning
confidence: 99%
“…Pass et al (2004) and Gordon et al (2003) have identified distinct signatures of prognosis in resected pleural mesothelioma, which interestingly were independent of histology subtype. More recently, Gordon et al (2005) used unsupervised clustering to identify three groups of tumors, two of which were comprised primarily of epithelial and biphasic tumors, respectively. Together, these results suggest that molecular signatures distinguish these subtypes in both peritoneal and pleural malignant mesothelioma.…”
Section: Discussionmentioning
confidence: 99%